The role of the opponent's head in perception of kick target location in martial arts - M. R. Incognito; T. Watson; T. Watson; G. Weidemann; G. Weidemann; G. Weidemann; K. A. Steel; K. A. Steel; K. A. Steel (Frontiers in Sports and Active Living)
Athletes in Martial Arts must anticipate the target of their opponent's kick or strike to avoid contact. Findings suggest that features, e.g., head and face may play a greater role in predicting opponent action intent compared to global movement information, however little research has explored the role of the head in action anticipation. The aim of this study was to examine the role of the head in predicting the target of a kicking action in martial arts. N = 76 volunteer participants (n = 32 athletes > 5 years of experience, n = 36 non-athletes with no experience) were asked to watch a series of video clips depicting various kicking techniques with differing levels of spatial occlusion of the head. These clips were also temporally occluded compelling participants to predict the landing target of each kick (i.e., head or chest). The hypothesis of the current study is that athletes would be more accurate than non-athletes, but there was no significant effect of expertise on accuracy. Both athletes and non-athletes performed well above chance level performance. Head occlusion did not significantly influence performance and did not interact with expertise, suggesting head and face information did not play a role in predicting opponent action intent. Across participants the landing target of the roundhouse kick was identified with greater accuracy than the front or the back kick. Additionally, participants identified kicks from the rear leg with greater accuracy than the front leg. These findings have significant implications for combat sports where athletes are required to anticipate the action intent of their opponent to formulate an effective defensive response.